WAYS TO IMPROVE THE FINANCING OF FIXED CAPITAL INVESTMENTS (American Journal of Business Management, Economics and Banking, 2025)
The article explores ways to improve the financing of investments in fixed capital. It analyzes current challenges in the allocation and utilization of financial resources, including insufficient private sector involvement, limited diversification of funding sources, and inefficiencies in investment management. The study highlights the importance of strengthening public-private partnerships, expanding the role of commercial banks and investment funds, and adopting innovative financial instruments to enhance investment efficiency. Additionally, the article examines international best practices and their applicability to the context of Uzbekistan, offering practical recommendations to optimize investment processes. The proposed measures aim to increase capital inflows, ensure financial sustainability, and support the modernization and competitiveness of the national economy.